The Role of Green Intellectual Capital Towards Masuliyyah Improving Environmental - Yudianto, Agus; Yuliawati, Tuti (Jurnal EMT KITA, 2024)
Environmentally, the company tries to achieve a level of environmental protection as part of the organization's sustainability goals. Meanwhile, socially, companies must also benefit society so that their existence gains social legitimacy. This research examines the influence of Green Intellectual Capital (GIC) towards Masuliyyah Improving Environmental Performance. In its implementation, green intellectual capital consists of Green Structural Capital (GSC), Green Human Capital (GHC), and Green Relational Capital (GRC), which reflect the intangible assets owned by the company, including knowledge, wisdom, experience, and innovation with attention to environmental welfare. This research is related to abstract ideas or theories and is often used to develop new concepts or provide new interpretations of existing theories. Through comprehensive literature analysis, this kind of research can produce research models that can be developed in further empirical research. The role of Masuliyyah green intellectual capital is environmentally friendly sustainability of human capital, the impression felt by organizational elements in their journey to discover and build organizational knowledge and improve the organization's environmental performance by focusing on needs, comfort, and a sustainable environment, but also providing the meaning of learning, innovation, maintaining friendly environment, support and attention to organizational elements to achieve common goals towards masuliyyah improving environmental performance.